[Saddle Road, NR. Port of Spain, Trinidad] - (:unkn) unknown (My University, 2009)
An aerial view of the Saddle Road, Maraval, Trinidad. The road, at bottom right hand corner of postcard and which could be mistaken for a steady stream, winds through the thickly wooded hillside where multiple tree tops all appear to merge into one another. Tree trunks look as thin as match sticks.
Colour: Black and White; Style: Landscape; Other: Bordered, Undivided
Keywords: Trinidad and Tobago; Postcards; Trinidad and Tobago--Aerial Views; Mountain roads--Trinidad and Tobago; Roads--Trinidad and Tobago; Mountains--Trinidad and Tobago; Forests and forestry--Trinidad and Tobago; Cities and towns--Trinidad and Tobago--Maraval; [1930]; Scenic byways--Trinidad and Tobago; Scenic overlooks--Trinidad and Tobago; Valleys--Trinidad and Tobago; Mountain passes--Trinidad and Tobago; Forest canopies--Trinidad and Tobago; Saddle Road (Trinidad and Tobago)